2017
DOI: 10.1007/s10544-017-0252-6
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon fabrication of hydrogel microstructures for excitation and immobilization of cells

Abstract: We investigate in vitro fabrication of hydrogel microstructures by two photon laser lithography for single cell immobilization and excitation. Fluorescent yeast cells are embedded in water containing the hydrogel precursor mixtures and cross-linking is used to selectively immobilize a particular cell. Cell viability within the hydrogel precursor is estimated using a life/dead assay and elastic and stiff hydrogel structures are fabricated, immobilizing cells in a microfluidic environment. Additionally, we demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…This study again showed the importance of high water content systems to reach good biocompatibility. The above-mentioned work, together with the 2P-microfabrication of waveguides for selective single yeast cells' immobilization and illumination 502 in PEG-DA hydrogel, is, to our knowledge, the only study in which cell-laden synthetic polymers have been used. Importantly, the writing process exhibited high cytotoxicity that can be attributed to the Irgacure 819 which, being an inefficient 2PI, requires higher laser doses.…”
Section: Two-photon Slmentioning
confidence: 99%
“…This study again showed the importance of high water content systems to reach good biocompatibility. The above-mentioned work, together with the 2P-microfabrication of waveguides for selective single yeast cells' immobilization and illumination 502 in PEG-DA hydrogel, is, to our knowledge, the only study in which cell-laden synthetic polymers have been used. Importantly, the writing process exhibited high cytotoxicity that can be attributed to the Irgacure 819 which, being an inefficient 2PI, requires higher laser doses.…”
Section: Two-photon Slmentioning
confidence: 99%
“…A second type of approach to cell trapping and sensing/manipulation by means of 3D MPL was given a few years later by Hasselmann et al [ 125 ]. In this study, single fluorescent E. coli cells were trapped by the fast (10–15 s) fabrication of PEGDA hydrogel (with Irgacure TM PIs) pillars (2 ) close to the cell.…”
Section: Laser-fabricated Active Microstructured Hydrogelsmentioning
confidence: 99%
“…( B ): Schematic illustration showing the cross-linking process in a cell-loaded hydrogel with a waveguide starting from a fiber connecting a cell for fluorescent excitation. Reprinted from [ 125 ]. ( C ): LSM images of 200 × 200 × 200 μm 3 RCPhC1-NB/SH-based cubes printed in the presence of living ASC–GFPs using 2 mol % DAS with respect to the photo-cross-linkable functionalities (left).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, realization of accurate structures becomes more challenging when the structural design has an open geometry, as the capillary forces caused by the evaporating developer lead to significant distortion or structural collapse . To date, most of the PEGDA formulations applied in 2PP exploit low-molar-mass PEGs (<750 g mol –1 ) to obtain an effective microfabrication process owing to a sufficiently high cross-linking density. , Nevertheless, it was reported that the processability of the latter is still prone to deformations associated with swelling and detachment from glass substrates. ,, Moreover, a narrow polymerization window has been observed, which limits tuning of microstructure dimensions and therefore the resolution of the printed structures . Scarpa et al.…”
Section: Introductionmentioning
confidence: 99%